Pengaruh Kompensasi Terhadap Kinerja Karyawan dengan Remunerasi sebagai Variabel Moderasi - Nabillatus Syuchriah; Suwandi Suwandi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to evaluate the impact of compensation on employee performance, with remuneration serving as a moderating variable in this relationship. A quantitative approach using the SEM PLS method was employed, involving 60 employees of PT. Yani Putra Ekspres selected through purposive sampling. The findings reveal that compensation has a significant effect on employee performance and can enhance motivation. However, other factors, such as job satisfaction and the work environment, were found to have a more dominant influence on performance. Additionally, remuneration proved to be an effective moderating variable in the relationship between compensation and employee performance. Therefore, it is recommended that the company pay greater attention to other aspects, such as human resource management, organizational culture development, and the creation of a supportive work environment, to sustainably improve employee performance.